Production of Cellulase by A. Niger and T. Reesei Under Solid State Fermentation Using Bagasse as Substrate - A Abdullah; H Hamid (Journal of Bioresources and Environmental Sciences, 2022)
Cellulase is a very important enzyme for ethanol production from lignocellulose and others. Bagasse is very good to be chosen as lignocellulosic material for cellulase production because it is cheap and already available in a huge amount. Solid-state fermentation has advantages than submerged fermentation because of its higher yield and activity. Cellulase production using solid-state fermentation has been researched by many people, but for different substrate, different pretreatment and different fungi producer, it is likely to have a different condition. It is very important to perform specific study to optimize cellulase production with specific substrate and specific fungi which available in Indonesia. Because large amount of fungi strains available so it is wise full if they are screened using effective and efficient methods. This research is started by initial screening of three strain of Trichoderma reesei and five strain of Aspergillus niger using Congo red dye staining on CMC agar plate. It is shown that a strain of Trichoderma reesei and two strains of Aspergillus niger has better activity than the others. Further screening is performed by conducting solid-state fermentation using bagasse by three best strains for five days. The activity of the cellulase is measured every 24-hour using Ghose method by dinitrosalicylic acid as reagent. The highest activity is shown by A.niger ITBCC L74 on third day at 0.525 Unit/gram